2020
DOI: 10.1038/s41563-020-0725-5
|View full text |Cite
|
Sign up to set email alerts
|

An integrated optical modulator operating at cryogenic temperatures

Abstract: Integrated photonic circuits (PICs) operating at cryogenic temperatures are fundamental building blocks required to achieve scalable quantum computing, and cryogenic computing technologies 1,2. Silicon PICs have matured for room temperature applications, but their cryogenic performance is limited by the absence of efficient low temperature electro-optic (EO) modulation. Here we demonstrate EO switching and modulation from room temperature down to 4 K by using the Pockels effect in integrated barium titanate (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…Furthermore, the preservation of the hysteresis has been proved at fast speeds (RF frequencies up to 60 GHz) [ 112 ] and, more recently, even at cryogenic temperatures (4 K), which could find application for quantum photonics. [ 117 ] Nevertheless, the key challenge for enabling a nonvolatile switching is that the best approach to induce the internal electric field to shift the hysteretic response is still unknown and will depend on the ferroelectric material and waveguide structure. For instance, a nonvolatile electro‐optical response was observed in a ring resonator based on a hybrid BTO/Si waveguide (Figure 13d).…”
Section: Nonvolatile Switching Enabled By Materials Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the preservation of the hysteresis has been proved at fast speeds (RF frequencies up to 60 GHz) [ 112 ] and, more recently, even at cryogenic temperatures (4 K), which could find application for quantum photonics. [ 117 ] Nevertheless, the key challenge for enabling a nonvolatile switching is that the best approach to induce the internal electric field to shift the hysteretic response is still unknown and will depend on the ferroelectric material and waveguide structure. For instance, a nonvolatile electro‐optical response was observed in a ring resonator based on a hybrid BTO/Si waveguide (Figure 13d).…”
Section: Nonvolatile Switching Enabled By Materials Integrationmentioning
confidence: 99%
“…quantum photonics. [117] Nevertheless, the key challenge for enabling a nonvolatile switching is that the best approach to induce the internal electric field to shift the hysteretic response is still unknown and will depend on the ferroelectric material and waveguide structure. For instance, a nonvolatile electrooptical response was observed in a ring resonator based on a hybrid BTO/Si waveguide (Figure 13d).…”
Section: Ferroelectricsmentioning
confidence: 99%
“…In addition, they can also be epitaxially grown as thin films on an Si substrate. Therefore, BTO emerges as a highly promising material to achieve Pockels electro-optic modulators integrated on a Si photonics platform [74][75][76][77]. First, S. Abel et al demonstrated a large Pockels effect in micro-and nanostructured BTO integrated on Si [74], as shown in Figure 5b.…”
Section: Optical Modulatorsmentioning
confidence: 99%
“…The integrated BTO/Si MZ modulator shows excellent V π L of 0.2 Vcm and αV π L of 1.3 VdB (~0.7 VdB when optimized), indicating~5.7 dB/cm (~3.0 dB/cm when optimized) and works at high speed of 25 Gbps, which is expected to reach data rates >50 Gbps by an adapted electrode design. Here, one feature of the optical modulators based on the Pockels effect are that they can be operated at cryogenic temperatures, whereas free-carrier effects-based optical modulators are restricted at low temperatures [76]. This is expected to encourage the use of Si photonics for quantum computing in the future.…”
Section: Optical Modulatorsmentioning
confidence: 99%
“…This may be mitigated with degenerate doping but at the cost of increased insertion loss. Noncarrier-based modulators using Franz-Keldysh or quantum-confined Stark effect [11] or Pockels effect [12] suffer from weak electro-optic strength at low temperature, thus requiring higher drive voltage and increased footprint, which limits the integration density of photonic integrated circuits for cryogenic applications.…”
Section: Introductionmentioning
confidence: 99%